The Influence of the Internet on Consumer Purchasing Behavior across Different Product Categories - ŠOSTAR, Marko; KUMAR, Kavya Sujith; DRAŽETIĆ, Magdalena (Theoretical and Practical Research in Economic Fields, 2025)
This study explores how the internet influences consumer purchasing behavior across various product categories, with particular attention to trust in online information and the impact of demographic factors such as age, income, and digital habits. A systematic literature review (SLR) was combined with an empirical survey conducted in Croatia involving 251 respondents. Non-parametric statistical tests were used to examine differences in online behavior based on age, income, employment status, and daily internet use. The internet exerts a stronger influence on purchasing decisions for categories like clothing, technology, and travel than for food or hygiene products. Trust in online information is also higher in product categories that typically require more research or personal investment. Younger users show significantly greater online engagement and reliance on digital content when shopping. However, no significant behavioral differences were observed based on employment or income levels. This study integrates quantitative analysis with bibliometric visualization, offering a comprehensive view of how the internet shapes consumer decisions across product types. It also reveals key psychological and demographic drivers of online behavior, providing a valuable framework for future research and digital marketing strategies. The sample is geographically limited to Croatia, which may affect the generalizability of the findings. Marketers and e-commerce platforms can tailor strategies based on product type and target demographic to enhance engagement and trust.